Recent advances and current challenges in suture and sutureless scleral fixation techniques for intraocular lens: a comprehensive review - Han Sun; Caixia Wang; Hong Wu (Eye and Vision)
Abstract Over the past two decades, both suture and sutureless techniques for scleral fixation of intraocular lenses have seen significant advancement, driven by improvements in methodologies and instrumentation. Despite numerous reports demonstrating the effectiveness, safety, and superiority of these techniques, each approach carries with it its own drawbacks, including an elevated risk of certain postoperative complications. This article delves into various surgical techniques for scleral fixation of posterior chamber intraocular lenses, discussing their procedural nuances, benefits, drawbacks, postoperative complications, and outcomes. Furthermore, a comparative analysis between suture and sutureless fixation methods is presented, elucidating their respective limitations and associated factors. It is hoped that this comprehensive review will offer clinicians guidance on how to individualize procedural selection and mitigate surgical risks, and thus achieve optimal visual outcomes. This review will also endeavor to provide guidance for future advancements in intraocular lens fixation techniques.